EFFECT OF INSECURITY ON AGRICULTURAL PRODUCTION IN OSE LOCAL GOVERNMENT AREA OF ONDO STATE, NIGERIA. - Abimbola Bridget, Falade; Olubanji Isa, Falade; Tope, Babatunde (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study investigated effect of insecurity on agricultural production in Ose Local Government Area of Ondo State, Nigeria. Four farming communities (40.0%) out of the total ten major farming communities were randomly selected from the local government area. Interview schedules were used to obtain information on socio-economic characteristics of the farmers, effects of insecurity, and the causes of insecurity on agricultural production from 120 farmers in the entire selected farming communities. The result shows that 96.7% of the respondents had various forms of formal education. All the identified perceived causes of insecurity on agricultural production using Likert scale were significant (Mean score > 3) in the study area, which include: herdsmen attack ( = 4.73), armed robbery ( = 4.60), and kidnapping ( = 4.48). The effects include: loss of profit, abandoned farmland, food shortage and loss of lives. It is therefore recommended that government security policies such as community policing, boarder security, anti-grazing laws; training, and regular retraining of security personnel on information and weapon handling are made and strictly implemented. Others include provision of employment by concerned authorities to reduce people engaging in kidnapping, armed robbery, and other unlawful activities, plus compulsory involvement of everybody in security business.